Characterizing Vegetation of Playa Lake Surfaces as Potential Grazing Resources for Arid Livestock in Western Rajasthan - Moharana, P.C.; Singh, J.P.; Patidar, Anil; Kumar, Mahesh (Annals of Arid Zone, 2023)
Playa lakes or Ranns characterized by ephemeral waterbody are the commonhydrological features in most arid lands. These water bodies hold rainwater for a fewmonths which gets dried up with time and letting adapted vegetation (grasses/herbs/shrubs) to germinate and grow. Local pastoralists depend heavily on these lands tograze their livestock, thus these vegetation resources come under high grazing pressure,creating a case of land degradation. In the present article vegetation resources of twoplaya lakes called Meetha (non-brackish) and Khara (brackish) Ranns from Jaisalmerdistrict have been reported. The results are based on field surveys, measurements andinformation gathered on ethnic importance of vegetation. The study found occurrencesof two true halophyte species within the Rann surface viz. Aeluropus lagopoides locallyknown as ‘Bukan’ and Cressa cretica called as ‘Oaen’. In the surrounding catchmentarea, Ochthochloa compressa (Gathia), Panicum turgidum (Murath) and Crotalaria burhia(Sinia) were dominant.